Tingkat Penerimaan SIPD RI berdasarkan UTAUT2 di Kabupaten Magelang - Ghanis Raisha Sandi Gavara; Joko Tri Nugraha; Eny Boedi Orbawati (FIA Unkris Press, 2026)
The rapid development of information technology requires government institutions to continuously improve the quality of digital services to support work effectiveness. One of these systems is the Regional Government Information System of the Republic of Indonesia (SIPD RI) administration module, which plays an important role in supporting regional financial administration processes. However, the implementation of the SIPD RI administration module in regional financial administration still faces several challenges, such as unstable server access, system complexity, user adaptation processes, and limited technical support that may affect system usage. This study employed a quantitative method with a modified Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model to analyze the factors influencing user acceptance. Data were collected through questionnaires distributed to 124 respondents from 31 Regional Apparatus Organizations (OPD) in Magelang, consisting of secretaries, heads of finance sub-divisions, and treasurers. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the assistance of SmartPLS 4.0 software. The results showed that effort expectancy and social influence had a positive and significant effect on behavioral intention. Furthermore, habit and behavioral intention had a positive and significant effect on use behavior. However, performance expectancy did not affect behavioral intention, and facilitating conditions also did not affect use behavior. These findings indicate that user acceptance of the SIPD RI administration module is more influenced by ease of use, social influence, and user habits rather than perceived usefulness and the availability of supporting facilities in system usage.